Implementasi Platform Media Sosial Sebagai Business Support oleh Pelaku Usaha Wisata di Kota Batam - Saut Pintubipar Saragih (Journal of Applied Informatics and Computing, 2018)
Batam City is a marine island which surrounded by shoes and baetiful marine tourism spots. Growth and existence of social media platform in the era of information technology particularly in tourism industry is very helpful either profitable for the perpetrators of the tourism industry because social media can be used for an effective and efficient in the information sharing to all tourists or potential visitors. In this research the objects will be examined is how the industry of tourism business entrepreneurs, operators or managers implement these social media platforms at supporting their business processes in order to get result in increasing tourist visits, increasing tourism objects and company popularity and eventually increasing the economic income consistently. In this research respondent that participated in this study were spread in 4 sub-districts, namely Galang sub-district, Bulang sub-district, Nongsa sub-district and Sekupang sub-district. There are several social media platforms used by the tourism industry entrepreneurs in Batam, they are Facebook, Instagram, Youtube, Whatsapp group, Line, Twitter and Linkedin. The platforms that 100% used by the entrepreneurs is facebook platforms which means all respondents are using this platform and followed by the Instagram consecutively. The type of account used by the marine tourism industry didn’t use a business account but some of them uses a regular account. Based on the results of the research data test, it was concluded that there were influences obtained by the marine tourism industry in Batam city in improving business, corporate profits and also increasing tourist visits through travel agencies provided or increased direct visits to managed tourism objects.